THE INFLUENCE OF THE APPLICATION OF MIND MAPPING TECHNIQUE AND READING ATTITUDE TOWARDS THE FOURTH GRADE PUPILS’ READING ABILITY OF ELEMENTARY PALM KIDS SCHOOL PALEMBANG - Ria Anggelia Tambun (Universitas PGRI Palembang, 2020)
The research was concerned with the inquiry on the influence of mind mapping and reading attitude on the fourth-grade pupils’ reading comprehension of Elementary School Palm Kids, Palembang. The problem of this study was to find out whether or not there was a significant effect of mind mapping on the fourth-grade pupils’ reading comprehension of Elementary School Palm Kids, Palembang. Mind mapping is a visual communication tool that uses visual symbols to express ideas and concepts, to convey meaning. Data collection employed pretest and posttest for experimental and control classes. Data analysis was undertaken by using paired sample t-test, independent sample t-test, and Two-way ANOVA. Findings showed that there was a significant effect of mind mapping and reading attitude on the fourth-grade pupils’ reading comprehension of Elementary School Palm Kids, Palembang. The conclusion suggests that the alternative hypothesis (Ha) was accepted while the null hypothesis (Ho) was rejected. It means that mind mapping was effective to improve pupils’ reading comprehension.